Managing the potential of small and medium-sized enterprises in business practice - (:unkn) unknown (Wydawnictwo Politechniki Łódzkiej, 2010)
The development of small and medium-sized enterprises is subject to numerous restrictions stemming both from their external environments, internal weaknesses and lack of resources in smaller business entities. On the other hand, these companies often have rich and strong potential which in appropriate conditions can become a powerful element of competitive advantage and the development factor of these companies. These conditions consist both of assistance activities carried out by institutions in business environment, the increase in the usage of management outputs and the professionalization of management processes in SMES sector. This monograph is devoted to the above-mentioned issues. Its aim is to present the areas and concepts of managing the potential of small and mediumsized enterprises. It concentrates mainly on the issues of social potential management, knowledge management, technical potential management and financial management in the companies of SMES sector. This monograph consists of thirteen chapters divided into three parts. In the first part the concepts of social potential management in small and medium-sized enterprises are presented. The attention is paid mainly to the importance of shaping and usage of organizational culture in the process of creating the competitiveness of smaller business entities. In this part, the possibilities to use flexible forms of employment and work organization in small and medium-sized enterprises are also presented. They often allow to increase the range of functioning decreasing at the same time the labor costs and the burdens of public law. Some place is also devoted to the attitudes towards the different elements of motivational systems in the companies of SMES sector and to the basic rules of building an effective team. The second part is devoted to knowledge management and technical potential management in the companies of SMES sector. The basic concepts of intellectual capital management and knowledge management in small and medium-sized enterprises are presented here. The next chapters deal with the issues of project management in smaller business entities. The attention is paid to the methods of collecting, accumulating and analyzing knowledge and experience gathered as the result of project realization and to the application of telecommunications services in the process of project management. The last chapter is devoted to the usage of network solutions, virtualization in the operations and value management of the contemporary enterprises. In the third part the examples of managing the potential of small and medium-sized enterprises in business practice are presented. The attention is paid to the importance of financial potential management. The financial conditions of small and medium-sized enterprises from the rural areas of Warmian-Masurian region are presented. There are also chapters devoted to key factors which affect marketing decision-making in small enterprises and to tendencies in customer service in transportation. The monograph ends up with a chapter presenting the barriers to development of small and medium-sized enterprises taking into consideration the peculiarity of L6dz voivodeship. The issue of managing the potential of small and medium-sized enterprises is relatively new in management. That is why it is important to conduct both theoretical and empirical research in this field. The authors hope that the papers presented in this monograph will help to understand better the concepts and the methods of the usage of social potential, technical potential and financial potential in the management of small and medium-sized enterprises. This monograph is designed for owners and managers of small and mediumsized business entities but also for people working in consulting firms, consultants and other institutions of business environment. Moreover. it seems that also academic teachers and students who have chosen specializations connected with entrepreneurship and management of small and medium-sized enterprises, will be interested in these issues. The research results can also inspire PhD students and young researchers to conduct further scientific research.

Rozwój małych i średnich przedsiębiorstw podlega licznym ograniczeniom, których źródłem jest zarówno środowisko zewnętrzne ich działania, jak również słabości wewnętrzne i niedostatki zasobowe mniej szych podmiotów gospodarczych. Z drugiej strony firmy te dysponują często bogatym i silnym potencjałem, który w odpowiednich warunkach może stać się skutecznym tworzywem przewagi konkurencyjnej i czynnikiem rozwoju tych przedsiębiorstw. Na warunki te składają się zarówno działania pomocowe realizowane przez instytucje otoczenia biznesu, jak również wzrost zakresu wykorzystania dorobku nauk o zarządzaniu oraz profesjonalizacja zarządzania w firmach sektora MSP. Tej właśnie problematyce poświęcono niniejszą monografię. Celem opracowania jest przedstawienie obszarów i koncepcji zarządzania potencjałem małych i średnich przedsiębiorstw. W pracy zwrócono uwagę przede wszystkim na problematykę zarządzania potencjałem społecznym, wiedzą i potencjałem technicznym oraz finansowym firm sektora MSP. Monografia składa się z trzynastu rozdziałów podzielonych na trzy części. W pierwszej części pracy zaprezentowano koncepcje zarządzania potencjałem społecznym małych i średnich przedsiębiorstw. Zwrócono tu przede wszystkim uwagę na znaczenie kształtowania i wykorzystania kultury organizacyjnej w rozwoju i procesie kształtowania konkurencyjności mniejszych podmiotów gospodarczych. Przedstawiono tu również możliwości wykorzystania elastycznych form zatrudnienia i organizacji pracy w małych i średnich firmach. Pozwalają one często na zwiększenie zakresu funkcjonowania przy jednoczesnym obniżeniu kosztów pracy oraz obciążeń publicznoprawnych. Rozważania poświęcono też postawom wobec poszczególnych składników systemu motywacyjnego w firmach sektora MSP, jak również podstawowym zasadom budowania efektywnego zespołu. Drugą część monografii poświęcono zarządzaniu wiedzą i potencjałem technicznym w firmach sektora MSP. Przedstawiono w niej podstawowe koncepcje zarządzania kapitałem intelektualnym oraz wiedzą w małych i średnich przedsiębiorstwach. Kolejne rozdziały poświęcono problematyce zarządzania projektami w mniejszych podmiotach gospodarczych. Zwrócono w nich uwagę na zasady zbierania, gromadzenia i analizowania wiedzy i doświadczenia kumulowanego w wyniku realizacji projektów organizacyjnych oraz na wykorzystanie usług telekomunikacyjnych w procesie zarządzania projektami. Ostatni rozdział poświęcono wykorzystaniu rozwiązań sieciowych i wirtualizacji w działalności i w zarządzaniu wartością współczesnych przedsiębiorstw. W trzeciej części przedstawiono przykłady zarządzania potencjałem małych i średnich przedsiębiorstw w praktyce gospodarczej. Zwrócono tu uwagę na znaczenie zarządzania potencjałem finansowym oraz przedstawiono sytuację finansową małych i średnich przedsiębiorstw z obszarów wiejskich Warmii i Mazur. Kolejne opracowania poświęcono kluczowym czynnikom decyzji marketingowych w małych przedsiębiorstwach oraz tendencjom rozwoju obsługi klienta w branży transportowej. Monografię kończy rozdział poświęcony barierom rozwoju małych i średnich przedsiębiorstw przedstawionym z uwzględnieniem specyfiki województwa łódzkiego. Problem zarządzania potencjałem małych i średnich przedsiębiorstw jest zagadnieniem stosunkowo nowym na gruncie nauk o zarządzaniu. Dlatego tak istotne wydaje się prowadzenie poszukiwań teoretycznych i badań empirycznych w tym obszarze. Autorzy wyrażają nadzieję, iż przedstawione w niniejszej monografii opracowania pozwolą lepiej zrozumieć koncepcje i metody wykorzystywania potencjału społecznego, technicznego oraz finansowego w procesie zarządzania małymi i średnimi przedsiębiorstwami. Monografia jest przeznaczona dla właścicieli i menedżerów zarządzających małymi i średnimi podmiotami gospodarczymi, a także dla pracowników firm doradczych, konsultingowych oraz innych instytucji otoczenia małego biznesu. Wydaje się ponadto, iż przedstawione treści znajdą uznanie wśród wykładowców akademickich oraz studentów, którzy w toku kształcenia wybrali specjalizacje związane z przedsiębiorczością lub z zarządzaniem małym i średnim biznesem. Wyniki dotychczasowych badań mogą stać się także inspiracją do dalszych poszukiwań naukowych, realizowanych w szczególności przez doktorantów i młodych pracowników nauki.
Red. naczelny : Wodziński, Piotr.
Red. nauk. Wydziału : Lewandowski, Jerzy
Red. serii : Wodziński, Piotr
Keywords: małe i średnie przedsiębiorstwa - zarządzanie; zarządzanie wiedzą; potencjał małych i średnich przedsiębiorstw; potencjał techniczny małych i średnich przedsiębiorstw; small and medium enterprises - management; management of knowledge; the potential of small and medium-sized enterprises; technical potential of small and medium enterprises